The Utilization of Technology-Based Media in Physical Education Learning Strategies at Madrasah Ibtidaiyah - Fitriyani; Friska Aulia; Annisa Nur Cahyani; Bardan Hanafi Alfian Luthfi; Meity Suryandari (Journal of Deep Learning, Computer Vision, and Digital Image Processing, 2026)
Purpose – This study examines the use of technology-based media in Physical Education learning at Madrasah Ibtidaiyah (MI) and Elementary School (SD) levels. It addresses the limitations of conventional instruction in explaining complex movement concepts and the need for more interactive, visual, and student-centered learning strategies in the digital era.Methods – A qualitative literature review was conducted using a systematic review procedure adapted from the PRISMA 2020 framework. Searches were carried out in Google Scholar and ERIC for publications from 2015 to 2025. From 145 initial records, 18 studies met the inclusion criteria and were synthesized qualitatively.Findings – The review shows that instructional videos, animations, simulations, interactive multimedia, mobile applications, and exergames can support students’ movement understanding, motivation, engagement, and participation in Physical Education learning. These media help present movement concepts visually and flexibly. However, their implementation is constrained by limited technological infrastructure, unequal access to digital resources, and insufficient teacher competence in integrating technology into movement-based instruction.Research implications – The findings suggest that technology integration should be supported by adequate infrastructure, teacher training, and pedagogical strategies that maintain active physical participation. Since this study is literature-based, its findings should be interpreted as synthesized evidence rather than direct empirical proof.Originality – This study provides a focused synthesis of recent literature on technology-based media in MI/SD Physical Education and identifies its pedagogical potential, implementation challenges, and future research directions.